Fundamentally Reforming the DI System: Evidence from Germany - Cao, Yaming; Fischer-Weckemann, Björn; Geyer, Johannes; Ziebarth, Nicolas (The Review of Economics and Statistics, 2026)
Abstract In 2001, Germany abolished public occupational disability insurance (ODI)—the second tier of its public DI system—for cohorts born after 1960. Using administrative data, we first document that, in the long run, overall DI inflows declined by roughly one-third. Second, using representative survey data, we document at best modest ODI insurance take-up responses in the private individual, risk-rated market, which lacks guaranteed issue. Third, an equilibrium model incorporating interactions between the public safety net, the first-tier public DI, and the private market reveals that coverage denials and weak insurance demand, driven by complementary social insurance, can explain the modest private ODI take-up response. Coverage gradients by income and health are thus substantial. Finally, counterfactual simulations highlight the limited scope of incremental reforms.